Experimental Study on Mechanical Properties of Fiber Recycled Concrete - GUAN Xiaodi; MA Di; WEI Huanhuan; KANG Jiawei; LEI Tianqi (Renmin Zhujiang)
In this paper,the influence of fiber types on the mechanical properties of recycled concrete materials is analyzed by controlling the fiber types in recycled concrete materials.Then,the influence of the diameter,length,and mass ratio of polypropylene fibers on the properties of recycled concrete materials is investigated by the design method of orthogonal tests.The results reveal that both plant fibers and straight polypropylene fibers could inhibit the damage to recycled concrete,while curved polypropylene fibers could not.The peak strength and deformation modulus of recycled concrete can be enhanced by plant fibers and straight polypropylene fibers,but with the increase in curing time,the strengthening effect of plant fibers decreases.At the same time,the mass ratio of polypropylene fibers has a significant impact on compressive strength and tensile strength,and the length of polypropylene fibers greatly affects tensile strength,which indicates that the mass ratio and length of fibers are important factors affecting the strength of recycled concrete materials.